2022
DOI: 10.3390/nano12213911
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Quantum Dot (Bi QD)/Polydimethylsiloxane (PDMS) Nanocomposites with Self-Cleaning and Antibacterial Activity for Dental Applications

Abstract: In the oral microenvironment, bacteria colonies are easily aggregated on the tooth-restoration surface, in the manner of a biofilm, which usually consists of heterogeneous structures containing clusters of a variety of bacteria embedded in an extracellular matrix, leading to serious recurrent caries. In this contribution, zero-dimensional (0D) bismuth (Bi) quantum dots (QDs) synthesized by a facile solvothermal method were directly employed to fabricate a Bi QD/polydimethylsiloxane (PDMS)-modified tooth by sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…On the contrary, it has been found through mechanical tests and thermal analyses that the mechanical behavior of polymeric coatings can be enhanced with the formation of nanocomposites by incorporating reinforcements with nanometric dimensions [ 4 ]. Furthermore, numerous investigations have been carried out, searching to modify other physicochemical properties of polysiloxanes, such as hydrophobicity [ 5 ], thermal conduction [ 4 ], antibacterial capacity [ 6 ], gas permeation [ 7 ], antifouling performance [ 8 ], and corrosion control [ 9 ], with nanocomposites being the main pathway that has successfully allowed the enhancement of these properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it has been found through mechanical tests and thermal analyses that the mechanical behavior of polymeric coatings can be enhanced with the formation of nanocomposites by incorporating reinforcements with nanometric dimensions [ 4 ]. Furthermore, numerous investigations have been carried out, searching to modify other physicochemical properties of polysiloxanes, such as hydrophobicity [ 5 ], thermal conduction [ 4 ], antibacterial capacity [ 6 ], gas permeation [ 7 ], antifouling performance [ 8 ], and corrosion control [ 9 ], with nanocomposites being the main pathway that has successfully allowed the enhancement of these properties.…”
Section: Introductionmentioning
confidence: 99%
“…These functional groups are capable of forming hydrogen bonds with water molecules, and thereby enhancing its hydrophilicity [ 40 ]. Previous work demonstrated that PDMS could remarkably reduce the surface energy of substrates for efficient self-cleaning, and simultaneously enhance their chemical and mechanical stability [ 41 , 42 ]. Here, after the individual incorporation of PDMS, the hydrophobicity of the PDMS@Cu (136.4°, Figure S5 ) slightly improves compared to that for the pristine Cu sponge (127.4°).…”
Section: Resultsmentioning
confidence: 99%
“…The study suggests that the antibacterial activity of Bi QDs can be significantly improved with the help of light illumination, even at low power density, because of the photothermal effect [20]. The photothermally-assisted superhydrophobic materials have emerged as promising candidates for a range of applications, including oil purification, waste oil collection, and solar desalination, thanks to their easy fabrication, low cost, flexibility, and ability to tune thermal conversion [21].…”
Section: Introductionmentioning
confidence: 99%